Transformasi Digital Dalam Pemasaran Rumah Sakit Berbasis Patient-Centered Care: Systematic Literature Review - Sadewo Yuri; Dewi Purnamawati (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
Advances in digital technology have triggered fundamental changes in hospital marketing strategies to improve service quality and competitiveness in the digital age. Digital transformation expands access to services through online platforms, improves operational efficiency through process automation, and strengthens real-time communication and interaction with patients, thereby shaping new expectations for fast, transparent, and responsive service. In line with these demands, the patient-centered care (PCC) approach has become increasingly crucial as it places patients’ needs, experiences, and satisfaction at the core of service delivery. This study aims to analyze the role of digital transformation in PCC-based hospital marketing through a systematic literature review. Data were collected from the PubMed, Scopus, ScienceDirect, and Google Scholar databases for the period 2015–2025. Based on the inclusion criteria, 8 relevant articles were identified and subsequently analyzed thematically.The study findings indicate that the use of social media, telemedicine, hospital information systems, and data-driven technologies significantly contributes to improving marketing effectiveness, expanding service reach, and strengthening patient engagement. The integration of digital transformation with PCC principles has proven effective in enhancing service quality, patient satisfaction, patient loyalty, and service process efficiency. Nevertheless, the implementation of this integration still faces various challenges, including low digital literacy, limited technological infrastructure, and resistance to organizational change. It can also be concluded that the integration of digital transformation and PCC requires technological readiness, the development of competent human resources, and patient-oriented service strategies as the keys to sustainably improving hospital quality, loyalty, and competitiveness.